Essential research methods for social work - Rubin, Allen; Babbie, Earl R. (Brooks/Cole empowerment series, 2013)
"Rubin and Babbie's ESSENTIAL RESEARCH METHODS FOR SOCIAL WORK provides students with a concise introduction to research methods that offers illustrations and applications specific to the field, as well as a constant focus on the utility of social work research in social work practice. Outlines, introductions, boxes, chapter endings with main points, review questions and exercises, and Internet exercises help students easily find the information and practice they need to succeed in the course. Part of the Brooks/Cole Empowerment Series, the third edition is up to date and thoroughly integrates the core competencies and recommended practice behaviors outlined in the 2008 Educational Policy and Accreditation Standards (EPAS) set by the Council on Social Work Education (CSWE)."--Publisher's website